UNGKAPAN HONORIFIK MUTLAK DALAM MENGAKOMODASI SAPAAN DAN VERBA KEISLAMAN PADA NOVEL KARYA OKKY MADASARI - Mochamad Nuruz Zaman (UIN Antasari Banjarmasin, 2018)
Abstract: This research is sociolinguistics approach of language contact of absolute honorifics in accommodating Islamic addresses and verbs on Okky Madasari’s novels. This is conducted by qualitatively descriptive by analyzing the data to be categorized the Islamic addresses and verbs in order to focus on those novels. Islamic addresses consist of nobility, general society, and Islamic verbs simultaneously able to well integrate on Okky Madasari’s novels. This development of Islamic addresses and verbs is substantially supporting theory of honorifics expressions focusing on Javenese lexicon and Indonesian language referent of respecting the utterance participants based on appropriate words.